Bone and Joint Infections in Children and Adolescents in Luanda, Angola - Pääkkönen Markus; Pelkonen Tuula; Joaquim Guilhermino; Bernandino Luis; Pöyhiä Tiina; Roine Irmeli; Peltola Heikki (Switzerland, 2022)
We reviewed the characteristics of children hospitalized for bone and joint infections in Luanda, Angola. In a retrospective chart review of 45 patients with childhood osteomyelitis or septic arthritis, 51% of the patients had sickle cell disease, and these patients presented with lower hemoglobin and needed blood transfusion more frequently (p < 0.05). Out of all patients, 64% underwent surgical procedures; a pathological fracture occurred in 31% of the patients.